2008
DOI: 10.1510/icvts.2008.188334
|View full text |Cite
|
Sign up to set email alerts
|

Does non-invasive ventilation associated with chest physiotherapy improve outcome after lung resection?

Abstract: A best evidence topic was constructed according to a structured protocol. The question addressed was whether the use of non-invasive ventilation (NIV) associated with chest physiotherapy (CPT) is effective in preventing respiratory complications in patients undergoing lung resection surgery. Of the 172 papers found using a report search, five presented the best evidence to answer the clinical question. The authors, journal, date and country of publication, study type, group studied, relevant outcomes and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…with no signs or symptoms of respiratory insufficiency, has been used in order to prevent respiratory complications. A literature review 25 has highlighted that NIV, associated with respiratory physical therapy, is a safe and effective resource to reduce and treat PO complications. In this study, 22% of NIV occured in patients who had been radiologicaly involved, however, without clinical manifestations, and 6% immediately after extubation, due to preoperative risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with no signs or symptoms of respiratory insufficiency, has been used in order to prevent respiratory complications. A literature review 25 has highlighted that NIV, associated with respiratory physical therapy, is a safe and effective resource to reduce and treat PO complications. In this study, 22% of NIV occured in patients who had been radiologicaly involved, however, without clinical manifestations, and 6% immediately after extubation, due to preoperative risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized study 26 used NIV in a prophylactic way in 500 patients, and demonstrated that NIV improves oxygenation, reduces respiratory complications and hospital readmissions. The preventive use of NIV within 48 hours after cardiac surgery, improves the values of ventilometry, respiratory muscle strength and peak of expiratory flow, which can prevent respiratory complications 5,25,26 . The subjects studied were characterized overweight (average BMI 28 kg/m²).…”
Section: Discussionmentioning
confidence: 99%
“…Uygulamaları; postoperatif toraks cerrahisinde noninvaziv mekanik ventilasyon (NİMV) kullanımı ile ilgili az sayıda araştırma olmasına rağmen, akciğer rezeksiyonu yapılan hastalarda NİMV'nin sadece akut solunum yetmezliği olan hastalarda değil, tüm hastalar için pnömoni, atelektazi ve bronşiyal konjesyon gibi postoperatif komplikasyonları azaltarak, iyileşmeyi hız-landıran, emniyetli ve etkili uygulamalar olduğu kabul edilmektedir (36).…”
Section: C Noninvaziv Mekanik Ventilasyon (Ni̇mv)unclassified
“…In patients who received low Vt (5 mL/kg) with a PEEP level of 5 cmH2O, as compared to a Vt of 10 mL/ kg and no PEEP, Michelet and coworkers [42] reported an attenuated systemic proinflamatory response, reduced extravascular lung water index, and improved PaO2 /FiO2 that allowed earlier extubation. Even though early postoperative use of continuous positive airway pressure (CPAP) or NIV with pressure support may result in faster improvement of arterial hypoxemia, their advantage in reducing the risk of PPC has been reported only in a few trials, and particularly when non invasive ventilatory support was associated with chest physiotherapy [43]. Besides Perrin's study [10] where NIV showed an improvement of oxygenation and a reduction in atelectasis, the benefits from non invasive ventilatory support are mainly reported in the treatment of rather than in prevention of postoperative acute respiratory failure [44,45].…”
Section: Preventing Postoperative Pulmonary Complications (Ppc)mentioning
confidence: 99%